2020
DOI: 10.2112/si95-137.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a Multi-Purpose Artificial Reef on Hydrodynamics, Waves and Long-Term Beach Morphology

Abstract: Impacts of a multipurpose artificial reef on hydrodynamics, waves and long-term beach morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Extensive reviews have been previously performed, such as [17,18] regarding artificial reef (submerged breakwater) design, [19] concerning shoreline response, and [10,20] related to the ecological function. As a result, various studies have been conducted to assess and improve the hydrodynamic [21,22], morphological [8,23], and ecological [24,25] functions; some few works address two functions together, e.g., [26]. It is worth mentioning that the methodologies and data used to evaluate each function have not changed much in time, which evidences some homogeneity in the field.…”
Section: Ecological Functionmentioning
confidence: 99%
“…Extensive reviews have been previously performed, such as [17,18] regarding artificial reef (submerged breakwater) design, [19] concerning shoreline response, and [10,20] related to the ecological function. As a result, various studies have been conducted to assess and improve the hydrodynamic [21,22], morphological [8,23], and ecological [24,25] functions; some few works address two functions together, e.g., [26]. It is worth mentioning that the methodologies and data used to evaluate each function have not changed much in time, which evidences some homogeneity in the field.…”
Section: Ecological Functionmentioning
confidence: 99%
“…Recent studies have shown that artificial coral reefs exhibit numerous advantages. In 2020, da Silva G. V. et al demonstrated that artificial reefs can effectively deflect longshore currents, alter sediment pathways, and thus induce long-term morphological changes [2]. Similarly, in 2020, Glarou M. et al found that artificial coral reefs can significantly increase fish species diversity, enhance coral cover and biomass, and facilitate interactions among marine organisms, all with positive effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…In cases where individual fish reefs can be clearly identified, we use the vector formed by the identified points P4 and P2 to determine the orientation of the fish reef, calculating the angle, as shown in Equation (2). This approach takes into account variations in identification conditions to enhance the accuracy and stability of posture estimation.…”
mentioning
confidence: 99%
“…Nevertheless, ARs were often based on structures that were not designed to meet the specific needs of the biota [9]. Therefore, several problems have been associated with AR deployments such as attraction and depletion of species stocks with socioeconomic conflicts [13,14], pollution, and toxicity [15], changes in species composition with the possible introduction and dispersion of exotic species [16], and changes in the hydrodynamics of the site [17].…”
Section: Introductionmentioning
confidence: 99%